Interaction Equivalency in Self-Paced Online Learning Environments: An Exploration of Learner Preferences - Rhode, Jason F. (International Review of Research in Open and Distributed Learning, 2009)
This mixed methods study explored the dynamics of interaction within a self-paced online learning environment. It used rich media and a mix of traditional and emerging asynchronous computer-mediated communication tools to determine what forms of interaction learners in a self-paced online course value most and what impact they perceive interaction to have on their overall learning experience. This study demonstrated that depending on the specific circumstance, not all forms of interaction may be either equally valued by learners or effective. Participants differentiated among the various learning interactions available and indicated that informal interactions were as important as formal interactions in determining the quality of the online learning experience. Participants also reported the activity of blogging as being equally valued and in some ways superior to instructor-directed asynchronous discussion via the discussion board in a learning management system.